Analyzing Female Employment Trends in South Asia - Fatima Najeeb; Matias Morales; Gladys Lopez-Acevedo (Institute of Labor Economics (IZA), 2020)
This paper studies employment patterns and trends in South Asia to shed light on determinants of extremely low female employment rates in the region. After a comprehensive literature review, we use employment data from about one hundred censuses and surveys from Afghanistan, Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka to compare employment trends across countries over time. We work through data inconsistencies to standardize definitions of variables to compare demographic and labor market determinants: age, sector, contract type, location, and education. We find that (i) overall since 2001, women's employment participation across South Asian countries has been low and broadly unchanged; (ii) the gender employment gap emerges more clearly in middle age brackets; (iii) rural female employment is higher than urban; (iv) agriculture is the economic sector accounting for the greatest share of female employment, although this is slowly changing in some countries, and; (v) women with mid-level education tend to have lower employment rates than those with both lower and higher education.
Keywords: J21; O53; 330; female labor force participation; South Asia